1986
DOI: 10.1002/1097-0142(19860415)57:8<1464::aid-cncr2820570805>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the esophagus. Complete response to combination chemotherapy

Abstract: A 55-year-old man had adenoid cystic carcinoma of the esophagus metastatic to the lungs and right supraclavicular fossa. He was treated with local radiation therapy to the esophagus and supraclavicular fossa, followed by combination chemotherapy with doxorubicin, mitomycin C, and 5-fluorouracil (5-FU). After a modest initial response, disease progression was noted in the pulmonary nodules. He was then treated with cisplatin, cyclophosphamide, vincristine, and doxorubicin. After two cycles of this regimen, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Since the first study, reported in 1954 by Gregg and Stamler (4), there have only been 17 cases reported in China and ~60 cases in other countries. Petursson (5) reviewed 45 cases of esophageal ACC. The mean age of patients with esophageal ACC was 65 years, and the male to female ratio was 3.4:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first study, reported in 1954 by Gregg and Stamler (4), there have only been 17 cases reported in China and ~60 cases in other countries. Petursson (5) reviewed 45 cases of esophageal ACC. The mean age of patients with esophageal ACC was 65 years, and the male to female ratio was 3.4:1.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the therapeutic effect of radiotherapy and chemotherapy for esophageal ACC remains controversial. The study by Petursson (5) reported that a combination of chemotherapy with cyclophosphamide, vincristine, adriamycin and cisplatin completely remitted ACC. The TNM staging of the patient in the present study was stage IIB.…”
Section: Discussionmentioning
confidence: 99%
“…The most common endoscopic findings include a fungating or polypoid mass rather than an ulcerative or infiltrative growth pattern. 5 Only three cases have been reported where they were presented as submucosal mass (Table 1). [8][9][10] One of the tumors was investigated by endoscopic ultrasonography.…”
Section: Discussionmentioning
confidence: 71%
“…3 The clinical behavior of esophageal ACC is not well known due to the small number of reported cases. [5][6][7] The average age of patients is 65 years, with a male to female ratio of 3.4 to 1. The most common symptom is progressive dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation